Fomo dan Tiktok: Analisis Media Sosial dan Kesehatan Mental dalam Perspektif Islam di Kalangan Mahasiswa Surabaya - Zainal Anshari; Mahillah; Nida Asni Furoidah; Nurul Hasan (STAI Bumi Silampari, 2026)
In today's era of technological advancement, TikTok has become a popular social media platform for many college students. Continuous TikTok use can trigger the emergence of Fear of Missing Out (FoMO). The purpose of this study was to determine the role of TikTok usage intensity as a mediator of FoMO on students' mental health and FoMO from an Islamic perspective. This study was quantitative with a cross-sectional design. This study was conducted on students in Surabaya. The sampling technique used was random sampling. Data collection was carried out through a research questionnaire consisting of several statements regarding FoMO, TikTok use, and mental health, as well as observations of the sample. The data analysis of this study was conducted through regression analysis on the PROCESS MACRO By Hayes system in the SPSS application. The results of this study indicate that FoMO has a very strong relationship with mental health, namely a p-value of very less than 0.05, namely <0.000. FoMO can also mediate the relationship between the intensity of TikTok use and mental health (? 0.64, p 0.000, 95% Cl [0.52-0.76]). From an Islamic perspective, FoMO can be prevented by practicing the attitudes of qanaah, gratitude, tawakkal, being humble, and establishing healthy relationships.